Indonesian Female Peacekeepers in The United Nations Peacekeeping Mission - Hutabarat, Leonard F. (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2017)
As peacekeeping has evolved to encompass a broader humanitarian approach, women personels have become increasingly part of the peacekeeping family. The UN has called for more deployment of female peacekeepers to enhance the overall â€œholisticâ€ approach to current UN peacekeeping operations. There is clearly more work to be done to integrate more female peacekeepers into UN missions. More skilled and trained female peacekeepers can only be an asset to future peacekeeping operations. In October 2000, the UN Security Council adopted Resolution 1325 on Women, Peace and Security. The resolution was hailed as a landmark resolution in that for the first time, the Security Council recognised the contribution women make during and post-conflict. Since the adoption of Resolution 1325, attention to gender perspectives within the international peace agenda has Â¬firmly been placed within the broader peace and security framework. This article explains the development of Indonesian female peacekeepers contribution in the period of 2009-20016 and argues why Indonesia needs to support and to consider deploying more female peacekeepers in UN peacekeeping operations.